Subsidi Perumahan, Migrasi dan Permintaan Rumah Studi Kasus Program Kpr Bersubsidi di Indonesia - Fourtiena, Elenka; Wisana, I Dewa Gede Karma (UI Scholars Hub, 2021)
This study examines the effect of the implementation of Kredit Pemilikan Rumah Fasilitas Likuiditas Pembiayaan Perumahan (KPR-FLPP) as subsidized mortgage on the recent migration rate and its impact for low-income households in Indonesia. Using the multiple linear regression method random effect model, this study analyzed the home ownership status of recent migrants with indicators of the average household’s per capita expenditure in the 2010-2019 Statistics Indonesia survey. The results show that the realization of KPR-FLPP has a negative effect on the migration rate. Meanwhile, the realization of KPR-FLPP has a negative effect on low-income households’ home ownerships rate, it is the same as the achievement of KPR-FLPP to reach low- income households had not been fully effective. Current evidence suggests that due to the lack of some population data information portal usage as a planning database to raise the accuracy to the low-income households as the main target. The Government of Indonesia should prioritize on the need for the formulation of subsidized mortgage policies necessary for the low-income households and encourage concerned stakeholders to develop the most appropriate policies such as the flat concept, which relevants of land-saving issues, as well as to supply the housing for low-income Keywords: rupiah movement; Chinese yuan; implicit currency basket households. Keywords: Subsidized mortgage, Migration, Low-Income Households, Housing